Use of Suture tightening automated device COR-KNOT® for minimally invasive heart valve surgery: Our initial experience in Bangladesh - Sazzad, Md Faizus (Bangladesh Journals Online (JOL), 2020)
10.3329/bhj.v34i2.44444